FREQUENCY OF NORMAL INTERICTAL EEG IN ADULTS PRESENTING WITH FIRST SEIZURE - CHANDIO, K; IRFAN, F; AZHAR , A; SHAFIQ, F; KHUDA, EI (Biological and Clinical Sciences Research Journal, 2024)
First-time seizure often triggers elaborate neurologic examination to define its etiology and assess the likelihood of its repetition. Objective: The study’s main objective is to find the frequency of normal interictal EEG in adults presenting with the first seizure. Methods: This cross-sectional study used data collected from 75 patients. Patient demographic details, seizure characteristics, and EEG findings were documented. EEG results were categorized as normal or abnormal (presence of epileptiform discharges, spikes, or sharp waves). Results: Data were collected from 75 patients with a mean age of 38.23 ± 12.09 years, ranging from 18 to 72 years. Among them, 53% were male, and 47% were female. Generalized tonic-clonic seizures were the most common, seen in 67% of patients, while 33% had focal seizures. EEG results showed that 43% had normal interictal EEGs, and 57% had abnormal findings. Imaging revealed structural abnormalities in 35% of patients, while 65% had normal imaging. At the 6-month follow-up, seizure recurrence was observed in 38% of those with normal EEGs and 58% in those with abnormal EEGs. Conclusion: It is concluded that a significant proportion of adults presenting with their first seizure may have normal interictal EEGs yet still face a risk of seizure recurrence.